Canadian military intelligence : operations and evolution from the October crisis to the War in Afghanistan - Charters, David A. (David Anderson), 1949- (Georgetown studies in intelligence history, 2022)
"David A. Charters has written a groundbreaking history of the influence of intelligence on eight Canadian Armed Forces operations between 1970 and 2010. Drawing on original documents, interviews, and other sources, the book examines the strategic, technological, and policy trends that impacted Canadian military intelligence; how the military intelligence organizations evolved; and how they supported operations and with what effect. The book makes three key points. First, that quality and adaptability could offset insufficient resources, but they could not guarantee operational success. Second, that belonging to international networks allowed the small Canadian military intelligence contingents to punch above their weight. Finally, by 2010, operational experience and internal reforms had transformed Canadian military intelligence and proven its value to commanders and civilian decision-makers"--